Modeling the flow of Oued Cherraa Basin (northeastern Morocco) using the SWAT model and evaluating model performance - Laaboudi Mohammed; Mezrhab Abdelhamid; Alioua Zahar Elkheir; Achebour Ali; Snaibi Wadii; Sahil Mohammed (E3S Web of Conferences)
River flow modeling is essential for water resource management, particularly in poorly gauged basins such as the Oued Cherraa in eastern Morocco. In these areas, modeling serves as an alternative to direct monitoring, helping to understand hydrological responses to water challenges such as floods, droughts and irrigation needs. The study used the SWAT model (ArcSWAT 2012 version) to simulate river flow in the Oued Cherraa basin. A sensitivity analysis, calibration and validation process were carried out using the sequential uncertainty adjustment method (SUFI-2), which optimized model parameters and ensured accurate reproduction of flows. The model was refined to better capture the basin’s complex hydrological processes, providing critical data for water management and planning. Key parameters analyzed include the deep aquifer percolation fraction (RCHRG_DP), the calibration coefficient for normal flow, and the curve number (CN2). The results showed a strong correlation between observed and simulated flow data. The mean monthly flow at Tazarhine (on Oued Zegzel) was 0.99 m³/s, with a simulated value of 1.076 m³/s during calibration and validation.